When Passion and Compassion Lead to a Technological Innovation: Telehealth Systems - Vicente, Ricardo; Jean-Jules, Joachim (Journal of Applied Business and Economics, 2022)
With the emergence of COVID-19, Telehealth became one of the subjects most discussed around the world as a solution to provide health service. Nowadays more than ever, we are facing a limitation of resources available, especially human and technological. As a consequence of these limitations, having in person appointment became almost impossible. Our aim in this article is to propose a better understand of the Telehealth and how it can be a good solution in this new context which we are living. We start discussing the specificities of the health environment and how the management literature applied to achieve success consider the passion and we make a review on the theories linked with the subject; then we propose some conjecture which can help the assimilation and implementation of a new system to provide. This paper concludes with a proposal of a multilevel modeling approach that enables stakeholders to gain a better understanding of the assimilation of information systems, based on their nature and the issues associated with their development.